Suggestion 2: Western Australian Electoral Distribution Commission Electoral Boundaries Review 2011 - Fullarton, Lex (Western Australian Government, Western Australian Electoral Commission, 2011)
It is proposed that the seat be continue to be known as North West to reflect its geographic position.